Certain investigations on the effect of nano metal oxide finishes on the multifunctional characteristics of cotton fabrics. (October 2013) - Sivakumar, A; Murugan, R; Sundaresan, K
The performance of ultraviolet protection, antimicrobial activity, soil release action and self-cleaning characteristics of nano zinc oxide (ZnO) with acrylic binder were assessed on the cotton fabric using pad-dry-cure method. Different precursors such as zinc chloride and zinc nitrate were used to synthesize nanoparticles by wet chemical technique. The synthesized nanoparticles were then characterized using Fourier transform infrared spectroscopy, particle size analyser, powder X-ray diffractometry and scanning electron microscopy. The nano ZnO finished cotton fabrics were tested for ultraviolet protection factor, antimicrobial activity, soil release action and self-cleaning action. The wash fastness of nano zinc oxide (ZnO) finished cotton fabrics after 5th, 10th, 15th and 20th washes were assessed. Also the ultraviolet protection factor values, percentage reduction in bacteria and soil release percentage in each washing stage are reported. The self-cleaning activity was assessed for 12, 24and 48 h duration by exposing 6% of coffee stain on the specimen fabrics to sunlight. The zinc oxide nanoparticle size of 24 nm was obtained from synthesis of zinc chloride as a precursor, and another nanoparticle size of 38 nm were obtained from synthesis of zinc nitrate as a precursor. The smaller nanoparticles (24 nm) show better results in terms of antimicrobial activity, soil release and self-cleaning action. In case of ultraviolet protection function, it was found that the fabrics treated with 38 nm nanoparticles exhibit higher ultraviolet protection factor values than the fabric treated with 24 nm nanoparticles. The durability of the imparted functions was in the range 25–38 washes for antimicrobial activity, soil release action and ultraviolet protection, respectively.